Variable Clinical Features in a Large Family With Diamond Blackfan Anemia Caused by a Pathogenic Missense Mutation in RPS19 - Cole, Sarah; Giri, Neelam; Alter, Blanche P.; Gianferante, D. Matthew (Frontiers in Genetics, 2022)
Introduction: Diamond Blackfan anemia (DBA) is an autosomal dominant ribosomopathy caused predominantly by pathogenic germline variants in ribosomal protein genes. It is characterized by failure of red blood cell production, and common features include congenital malformations and cancer predisposition. Mainstays of treatment are corticosteroids, red blood cell transfusions, and hematologic stem cell transplantation. Despite a better understanding of the genotype of DBA, the biological mechanism resulting in the clinical phenotype remains poorly understood, and wide heterogeneity can be seen even within a single family as depicted here. Case Description: Thirty family members enrolled in the National Cancer Institute inherited bone marrow failure syndromes study were evaluated with detailed medical questionnaires and physical examinations, including 22 in the family bloodline and eight unrelated partners. Eight participants had been previously told they had DBA by clinical criteria. Targeted germline RPS19 testing was done on all family members. A pathogenic heterozygous missense mutation in RPS19 (p.R62Q, c.185G>A) was detected in ten family members, including one person previously presumed unaffected. Eight family members presented with macrocytic anemia in infancy; all of whom were responsive to prednisone. Four became treatment independent; however, one individual became transfusion-dependent 36 years later following an episode of pneumonia. One prednisone responsive individual electively discontinued steroid treatment, and lives with severe anemia. One prednisone responsive individual died at age 28 from a stroke. Two family members developed colorectal cancer in their fifties; one had never required treatment for anemia. None had major congenital anomalies. Discussion: This large family with DBA demonstrates the heterogeneity of phenotypes that can be seen within the same genotype. Most family members presented with steroid-responsive anemia in infancy and subtle congenital malformations, findings consistent with recent genotype-phenotype studies of RPS DBA. However, two family members were relatively unaffected, underscoring the importance of further studies to assess modifier genes, and epigenetic and/or environmental factors which may result in normal erythropoiesis despite underlying ribosome dysfunction. This large, multigenerational family highlights the need for individualized treatment, the importance of early cancer surveillance even in individuals with clinically mild phenotypes, and the benefit of long-term follow-up to identify late complications.